2019
DOI: 10.1021/acs.jnatprod.9b00567
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Pterocarpans and Coumestans from Lespedeza bicolor

Abstract: Chromatographic purification of a methanol extract of the roots of Lespedeza bicolor led to the isolation of four new pterocarpans (1− 4), two new coumestans (6 and 7), two new arylbenzofurans (8 and 9), and the known pterocarpan 1-methoxyerythrabyssin II (5). Their structures were identified using NMR spectroscopy, UV spectroscopy, and mass spectrometry. Cytotoxicity assays showed that compounds 1−9 exerted antiproliferative effects on blood cancer cells. Of these compounds, 1 and 6 induced mitochondrial depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 22 publications
(35 reference statements)
0
22
0
Order By: Relevance
“…The obtained extract of L. bicolor root bark (1.7 g) was chromatographed on a polyamide column (80 g, 50-160 µm, Sigma-Aldrich, St. Louis, MI, USA). The column was eluted with a hexane-CHCl 3 solution system with gradually increasing CHCl 3 amounts (hexane/CHCl 3 , 1:0, 100:1, 50:1, 40:1) to give fractions 1-13 and then with a CHCl 3 -EtOH solution system with gradually increasing EtOH amounts (CHCl 3 /EtOH, 1:0, 100:1, 50:1, 40:1, v/v) to give fractions [14][15][16][17][18][19][20]. The fractions containing polyphenolic compounds according to TLC HPLC data were subjected to further purification.…”
Section: Extraction and Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…The obtained extract of L. bicolor root bark (1.7 g) was chromatographed on a polyamide column (80 g, 50-160 µm, Sigma-Aldrich, St. Louis, MI, USA). The column was eluted with a hexane-CHCl 3 solution system with gradually increasing CHCl 3 amounts (hexane/CHCl 3 , 1:0, 100:1, 50:1, 40:1) to give fractions 1-13 and then with a CHCl 3 -EtOH solution system with gradually increasing EtOH amounts (CHCl 3 /EtOH, 1:0, 100:1, 50:1, 40:1, v/v) to give fractions [14][15][16][17][18][19][20]. The fractions containing polyphenolic compounds according to TLC HPLC data were subjected to further purification.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…A comparison of the HPLC profiles of L. bicolor stem bark and root bark showed that compounds 7 and 8 are also present in L. bicolor stem bark but in smaller amounts than in root bark (Figure 2). Recently, Korean colleagues isolated five pterocarpans, two new coumestans, and two new arylbenzofurans with prenyl and geranyl substituents in their structures [14]. These isolated compounds contain a methoxy group at C-1 and exhibited antiproliferative effects on human leukemia cells.…”
Section: Isolation and Structure Elucidation Of Compounds 1-8mentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were treated with different concentrations of HEDO (3,5,10,20,50, and 100 µM). Cell viability was assessed using an MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt) assay, as described in a previous paper written by the authors of this study [18].…”
Section: Antiproliferation Assaymentioning
confidence: 99%
“…Hydroxylated benzofurans are ubiquitous structural motifs of various natural products and bioactive molecules. [1] As shown in Scheme 1, these molecules contain at least one free hydroxyl group attached to the benzene ring with different substituent patterns,w hich have attracted much attention owing to their wide spectrum of biological activities.F or example,a saphytoestrogen, coumestrol (with one hydroxyl at C6) exhibits diverse activities against cancer,n eurological disorders,a nd autoimmune diseases. [2] Them arine natural product liphagal (with two hydroxyl groups at C5 and C6) can modulate human phosphatidylinositol-3-kinase (PI3K) sig-nalling pathway, [3] which may have therapeutic potential for the treatment of autoimmune disorders,c ardiovascular diseases,a nd cancer.…”
Section: Introductionmentioning
confidence: 99%